Utilisation of Poster Information Media as an Educational Tool for the Fish Farmers in Tanjung Raya District, West Sumatra - Nurkhalila Fajrini; Yesi Puspita; Prima Fithri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The Nagari Tageh concept, originally initiated earlier, has evolved into a broader scope, extending beyond the confines of the Covid-19 pandemic, with the overarching goal of accelerating the realization of Nagari Mandiri. The Tanjung Raya community's economic hardships, notably the Fish Farmers of Lake Maninjau, prompted our community engagement team to fortify the ‘New Nagari Tageh’ concept. The activity commenced with developing customized posters catering to the community's specific needs, encompassing imagery, color schemes, and language. Those posters served as a medium for publicizing the Nagari Tageh program in the Agam Regency. Furthermore, our community engagement team engaged in intensive discussions with the Agam Regency government, involving the Regional Development and Planning Agency (DPMD), to gain a better understanding of the on-ground situations and conditions faced by fish cage farmers in the Tanjung Raya subdistrict. Subsequently, our team provided counseling and further guidance to the fish cage farmers, ensuring the successful implementation of the ‘New Nagari Tageh’ concept. This holistic approach aimed to equip the community with the necessary knowledge and education to mitigate the impact of the Covid-19 pandemic across various aspects of community life. Furthermore, it sought to rejuvenate the economic prospects of the fish cage farmers in the Tanjung Raya subdistrict, embodying the essence of the ‘New Nagari Tageh’ concept.